Von Aachen bis Akkon (Heidelberg University Publishing (heiUP), 2023)
Published on the occasion of Hubert Houben’s 70th birthday, this volume focuses on border crossings as one of the topics dear to the jubilarian. By starting from a concept of borders as a social construct, the authors look at selected cases of transcending spatial, cultural and legal boundaries in the Middle Ages. The resulting complexity and multi-perspectivity reflects different research methods and traditions, revealing a broad spectrum of possible approaches to the topic of border crossings.